(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Non-rigid Structure from Motion (NRSfM) is a classical computer vision problem. And the main methods used to solve it are in general based on shape models or trajectory models. This paper will provide an overview over kinds of solutions proposed in these researches. It not only gives out the theoretical insights proposed by researchers in recent years, but also discusses them with their pros and cons. At the same time, the progress of the research about this topic is described in detail and its long-term trend is introduced at the end. This paper is very easy to understand, which mainly introduces two practical, everyday models for the NRSfM problem, namely trajectories based model and shape based model. Both of them are based on matrix factorization technology. Inevitably, some relevant optimization methods are mentioned to solve the projection matrix and corresponding coefficients effectively.